1971
DOI: 10.1097/00004032-197107000-00006
|View full text |Cite
|
Sign up to set email alerts
|

The Question of Safe Radiation Thresholds for Alpha Emitting Bone Seekers in Man

Abstract: The Evans hypothesis derived from the study of radium-exposed persons includes two major points: (a) the linear model of radiation carcinogenesis is incorrect, and (b) "practical" and/or absolute thresholds exist below which human radiation carcinogenesis does not occur.Analysis presented here indicates that neither aspect of this hypothesis can be supported, either from the study of residual radium burden or from cumulative rad exposure.This analysis in no way attempts to show that "practical" or absolute thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1979
1979
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…The LNT assumption of radiation risk is the subject of much speculation and discussion (Cohen 1995, Académie des Sciences 1997, Clarke 1998, Tubiana 1998, Kellerer 2000, Kellerer and Nekolla 2000, Trott and Rosemann 2000 and is challenged by some who claim that a threshold dose exists below which radiation does not cause any effects (Becker 1997, Bond et al 1996, Tubiana 2000, Duport and Meadley 1997 and by others who claim that, on the contrary, the effect of radiation at low dose is far greater than that predicted by the linear extrapolation to zero dose currently applied by the ICRP (Sternglass 1963, 1968, Gofman and Tamplin 1971, Stewart and Kneale 1990, Edwards 1997. There are those amongst the first group, proponents of hormesis, who even suggest that low doses of radiation can cause a beneficial health effect (Luckey 1980, Sagan 1989, Kesavan and Sugahara 1992.…”
Section: Introductionmentioning
confidence: 99%
“…The LNT assumption of radiation risk is the subject of much speculation and discussion (Cohen 1995, Académie des Sciences 1997, Clarke 1998, Tubiana 1998, Kellerer 2000, Kellerer and Nekolla 2000, Trott and Rosemann 2000 and is challenged by some who claim that a threshold dose exists below which radiation does not cause any effects (Becker 1997, Bond et al 1996, Tubiana 2000, Duport and Meadley 1997 and by others who claim that, on the contrary, the effect of radiation at low dose is far greater than that predicted by the linear extrapolation to zero dose currently applied by the ICRP (Sternglass 1963, 1968, Gofman and Tamplin 1971, Stewart and Kneale 1990, Edwards 1997. There are those amongst the first group, proponents of hormesis, who even suggest that low doses of radiation can cause a beneficial health effect (Luckey 1980, Sagan 1989, Kesavan and Sugahara 1992.…”
Section: Introductionmentioning
confidence: 99%
“…2 that the dose-effect relationship is non-linear. Gofman and Tamplin 62 have suggested that these data are consistant with linearity but the chance that this is so is 10 8 to 1 against. 55 External radiations protection standards are, in part, based upon data on the incidence of leukemia and other cancers in the survivors of the nuclear weapons explosions at Hiroshima and Nagasaki.…”
Section: The Concept Of An "Effective Threshold" Is Of Great Interestmentioning
confidence: 99%
“…Other publications during this period used data from the radium programs to derive alternate dose-response functions for radium-induced malignancies (Hems 1967;Goss 1970;Gofman and Tamplin 1971). These analyses usually forced linear functions through the data without testing the resulting curves for goodness of fit.…”
Section: Risk Estimates For Radium-induced Malignanciesmentioning
confidence: 99%
“…Goss concluded that neither of these probabilities was small enough to reject the linear hypothesis. Gofman and Tamplin (1971) tested individual dose ranges from the data of Evans et al (1969) and Finkel et al (1969) against a linear expression of the form…”
Section: Risk Estimates For Radium-induced Malignanciesmentioning
confidence: 99%
See 1 more Smart Citation